Adenosine A2a receptor in Experimental Periodontitis - Nathalie Paladines; Ana Carolina Morandini, DDS MDS PhD (Elsevier, 2024)
OBJECTIVES: Our previous work has shown the role of adenosine in mitochondrial health to regulate IL-1-mediated inflammation in human gingival fibroblasts, and the protective role of enzyme CD73, which is the final step to generate adenosine extracellularly, in mediating osteoclastogenesis and the hyper inflammatory response of gingival fibroblasts. Adenosine A2a receptor (A2aR) agonist (CGS21680) has been associated with anti-inflammatory effects in models of sepsis, articular chondrocyte inflammation, and oral mucositis in vitro as well as particle-induced inflammatory bone destruction in vivo. This study examined the effects of A2aR agonist CGS 21680 in a mouse model of ligature-induced periodontitis. METHODS: Mature adult mice (C57Bl/6J) underwent ligature placement on the maxillary second molar to induce periodontitis. The unligated contralateral molar tooth served as an internal control. For the following 8 days, the mice received intra-peritoneal injections of A2aR agonist (CGS21680, 0.1 mg/Kg) or a saline control. After 8 days, gingival tissues and maxillae were harvested. The maxillae underwent micro-CT analysis to measure alveolar bone loss and the gingival tissues were processed for protein analysis through immunoblot. RESULTS: Micro-CT analysis demonstrated mice that received A2aR agonist had significantly less bone loss compared to the control group. Protein analysis of gingival tissue showed periodontitis induced higher IL-1 levels compared to the unligated side and decreased IL-1b in A2aR-treated mice compared to control animals. CONCLUSIONS: In conclusion, A2aR-treated mice were protected from ligature-induced periodontitis and displayed less gingival IL-1 levels.